2007
DOI: 10.1111/j.1442-2042.2007.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of glutathione‐S‐transferase P1 (GSTP1) polymorphism with urothelial cancer susceptibility and myelosuppression after M‐VAC chemotherapy

Abstract: Aim: Glutathione-S-transferase P1 (GSTP1) detoxifies a wide range of endogenous and exogenous carcinogens and anticancer agents such as cisplatin and doxorubicin. The aim of this study was to examine the association between GSTP1 polymorphism and both urothelial cancer susceptibility and adverse events of M-VAC (methotrexate, vinblastine, doxorubicin and cisplatin) chemotherapy in Japanese urothelial cancer patients. Methods: This cohort consisted of 179 urothelial cancer patients and 225 healthy controls matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…36 In a group of 46 patients with bladder cancer, individuals with the GSTP1*Val allele showed a higher myelotoxicity after the chemotherapy regimen M-VAC. 37 Our finding of a reduced hematoxicity after chemotherapy in AML patients with the GSTP1*105Val allele, based on the analysis of 832 treatment cycles from 307 patients, appears to be in contrast with these data. One hypothesis could be that different from solid tumors, residual hematopoiesis is severely impaired in AML at diagnosis, and an improved eradication of leukemic cells after chemotherapy might result in a more rapid restoration of normal hematopoiesis.…”
Section: Gst Genotypes and Survivalcontrasting
confidence: 68%
“…36 In a group of 46 patients with bladder cancer, individuals with the GSTP1*Val allele showed a higher myelotoxicity after the chemotherapy regimen M-VAC. 37 Our finding of a reduced hematoxicity after chemotherapy in AML patients with the GSTP1*105Val allele, based on the analysis of 832 treatment cycles from 307 patients, appears to be in contrast with these data. One hypothesis could be that different from solid tumors, residual hematopoiesis is severely impaired in AML at diagnosis, and an improved eradication of leukemic cells after chemotherapy might result in a more rapid restoration of normal hematopoiesis.…”
Section: Gst Genotypes and Survivalcontrasting
confidence: 68%
“…GSTP1, which is involved in the detoxification of carcinogenic polycyclic aromatic hydrocarbons, has been investigated extensively in relation to different types of cancer, such as breast cancer [57], [58], bladder cancer [59], [60], oesophageal cancer [61], [62], and so on [5]. Previous results of the studies on the association of GSTP1 Ile105Val polymorphism with prostate cancer risk were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have shown that patients with G/G genotype present less toxicity (Oldenburg et al, 2007a , b ; Goekkurt et al, 2009 ; Kim et al, 2009 ) with more survival (Goekkurt et al, 2006 ; Ruzzo et al, 2006 ; Ji et al, 2013 ) and better therapy response (Sun et al, 2010 ; Yang et al, 2012 ). On the other hand, the G allele has been associated with a risk of myelosuppression, polyneuropathy, and toxicity (Yokomizo et al, 2007 ; Joerger et al, 2012 ; Windsor et al, 2012 ; Rednam et al, 2013 ). In ovarian cancer, the A allele is related to better PFS and OS (Khrunin et al, 2010 ).…”
Section: Pharmacokinetic Mechanismsmentioning
confidence: 99%